Carboxymethyl chitosan-kaolinite composite hydrogel for efficient copper ions trapping. Issue 2 (April 2019) - He, Guanghua; Wang, Cheng; Cao, Jilong; Fan, Lihong; Zhao, Sa; Chai, Yun
Abstract: The qualified sorbents for removing heavy metals from wastewater, which possess high adsorption capacity, low cost and the ability of rapid separation and regeneration, are urgently needed. Herein, we reported a kind of carboxymethyl chitosan-kaolinite composite hydrogel with excellent mechanical properties, low cost and high Cu 2+ removal efficiency. This polyampholyte hydrogel was well designed and prepared through a simple Schiff base reaction. Due to the remarkable mechanical strength, the composite hydrogel could be fast separated, easily regenerated and highly reused. The adsorption capacities for Cu 2+ were reaching up to 206 mg g −1 attribute to the existence of the large number of active groups. The adsorption could be conducted in a wide pH range of 2.5 to 6 and the equilibrium fast reached in 300 min due to its excellent water penetration for highly accessible to metal ions. These results indicated that carboxymethyl chitosan-kaolinite composite hydrogel were effective adsorbents for trapping Cu 2+ from wastewater, which would provide a new idea for removal of heavy metal ions.